2020
DOI: 10.1016/j.sjbs.2020.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antinematicidal metabolites from Streptomyces cuspidosporus strain SA4 against selected pathogenic bacteria, fungi and nematode

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Studies have already demonstrated actinomycetes metabolites active against bacteria (27), fungi (28), viruses (29), nematodes (30), and insects (31), as well as compounds with antitumor (32) and herbicide (33) activities. Some species can also produce enzymes of industrial interest, such as chitinases, cellulases, and amylases (34), and enzymes involved in plant growth promotion, like phosphatases and nitrogenases (35).…”
Section: Actinomycetes: a Rich Source Of Bioactive Compoundsmentioning
confidence: 99%
“…Studies have already demonstrated actinomycetes metabolites active against bacteria (27), fungi (28), viruses (29), nematodes (30), and insects (31), as well as compounds with antitumor (32) and herbicide (33) activities. Some species can also produce enzymes of industrial interest, such as chitinases, cellulases, and amylases (34), and enzymes involved in plant growth promotion, like phosphatases and nitrogenases (35).…”
Section: Actinomycetes: a Rich Source Of Bioactive Compoundsmentioning
confidence: 99%
“…A large number of acid compounds such as chloroacetic acid, furandicarboxylic acid, formic acid, pentacosanoic acid, hexadecanoic acid, and benzenedicarboxylic acid were a main type of antifungal production. Benzenedicarboxylic acid possessing high peak area is a main metabolite of S. cuspidosporus with high antagonistic activity against pathogenic bacteria, fungi, and nematode ( Sholkamy et al, 2020 ). Chloroacetic acid and hexadecanoic acid had the potential for controlling Colletotrichum gloeosporioides ( Rajaofera et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial Resistance (AMR) of pathogenic bacteria emerges when the microorganisms acquire resistance to antibiotics, enabling them to no longer respond to antibiotics [38]. Crude extract from M1 and M3 isolates were screened for antibacterial activity against ten bacterial pathogens, and two fungus strains, using the agar well diffusion method [39] (6 mm). As previously known, fungal pathogens have been responsible for significant agricultural losses caused by the plant diseases they produce; they are also the origin of many medically related illnesses [40].…”
Section: Determination Of Anti-microbial Property By Agar Cup Methodsmentioning
confidence: 99%